INVESTIGATION OF ARSENIC REMOVAL FROM GROUNDWATER BY NANO-DIMENSIONAL MnO2 AND FeOOH COATING ON CALCINATED LATERITE - Con, Tran Hong; Loan, Dong Kim; Cuong, Le Manh (Vietnam Journal of Science and Technology, 2012)
The arsenic contamination in groundwater is real problem in Vietnam threatening health of millions people (M. Berg et al., 2001)[1]. The reason was concerned to natural processes happening in underlying layers of the basin areas including Hanoi in the North and Hochiminh, the biggest City in the South of Vietnam. The highest risk potential is determined in the areas of Mekong River, Red River and Ma River deltas. Therefore arsenic treatment for drinking water in Vietnam is recently urgent requirement [2]. Our investigation based on the advanced adsorption of nano-dimensional MnO2 and FeOOH preparing in ethanol – water media [3]. The concentration of ethanol in solution played important role in nano-particles’ formation and anticoagulation [10]. Dimension of MnO2 particles was appropriately 50 nm diameter determined by TEM method; those of FeOOH particles were 30 nm long and 10 nm wide. The MnO2 and FeOOH particles in colloidal solution then were coated on calcinated laterite grains to create high performance adsorption material for arsenic removal from groundwater. The materials surface was studied by SEM method. The adsorption capacity of materials was determined. The maximum adsorption of arsenic on nano-MnO2 coated material was 125.89 mg per gram and on nano-FeOOH coated material was 91.74 mg per gram. The optimum conditions for arsenic treatment as well as adsorbent’s regeneration were investigated.